Social Media Exposure and Civic Competencies of College Students in a State University: Basis for a Learning Enrichment Plan - Fontanilla, Jay Carlo A.; Ebro, Eric D. S.; Ladiero, Joshua S.; Marty, Mary Grace A.; Quinte, Jessie P.; Tambalgue, Marife (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
In the contemporary digitally interconnected society, social media exerts a pivotal influence on acquiring knowledge and skills, particularly among the youth. This research investigated the impact of social media exposure on the civic competencies of university students, aiming to develop an enrichment learning plan. Using a stratified sampling method, a survey questionnaire was administered to 100 students from the College of Teacher Education (CTE) BSED Department across all academic levels at a state university. The study utilized Pearson correlation analysis, revealing a significant and strong positive relationship between social media exposure and civic competencies. Key contributors to civic competencies identified were civic knowledge, 21st-century skills, and political engagement. The findings indicated that increased engagement with social media enhances students' civic competencies, as shown by a strong positive correlation (r = 0.69, p < 0.05). These results underscore the potential of social media as a valuable educational tool, suggesting the need for its integration into curricula to foster informed and active citizenship among students.